Mahasiswi FISIP USU, Yuliance Alua Mengajak Anak Tunanetra Yayasan Pendidikan Tunanetra Untuk Meningkatkan Kepercayaan Diri - Berlianti, Berlianti; Yuliance, Yuliance (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
North Sumatra Blind Education Foundation (YAPENTRA) in Tanjung Morawa, Deli Serdang district. This foundation is a foundation that educates blind children and children with special needs in general, the focus of the author is blind children. Blind people are someone who has visual impairments. the author's goal is to find out the problems or obstacles faced by blind children. The problem or obstacle they experience is a lack of self-confidence. Confidence is the ability to believe in our abilities or the ability to develop positive judgments for ourselves or our families and the environment. The method used is group work with a non-directive approach where the author involves children in solving the obstacles they face. This foundation not only provides education but provides various skills and training to develop the talents of blind children, so that blind children can grow to become more independent and more creative individuals.